Synephrine, a Component of Evodiae Fructus, Constricts Isolated Rat Aorta via Adrenergic and Serotonergic Receptors - Tomoko Hibino; Mitsutoshi Yuzurihara; Yoshio Kase; Atsushi Takeda (Elsevier, 2009)
We investigated the effects of Evodiae Fructus and synephrine, one of the components of Evodiae Fructus, on blood vessels. We found that Evodiae Fructus (1 × 10−4 g/mL) had constrictive effects on rat aorta. The vasoconstrictive effects of Evodiae Fructus were significantly inhibited by pretreatment with prazosin (adrenergic α1-receptor antagonist), BRL15572 [5-hydroxytryptamine (5-HT)1D antagonist], and ketanserin (5-HT2A antagonist), but its vasoconstrictive effects were not inhibited by pretreatment with SB216641 (5-HT1B antagonist) or propranolol (adrenergic β-receptor antagonist). These results suggest that Evodiae Fructus constricts rat aorta via adrenergic and serotonergic receptors. We also investigated the constrictive effects of synephrine on blood vessels. The vasoconstrictive effects of synephrine (1 × 10−7- 3 × 10−5 mol /L) were significantly inhibited by pretreatment with prazosin, BRL15572, and ketanserin. However, its constrictive effects were not inhibited by pretreatment with SB216641 and propranolol. The pA2 values of prazosin or ketanserin were nearly equal between Evodiae Fructus and synephrine. Because the constrictive effects of both Evodiae Fructus and synephrine were exerted via adrenergic α1-receptors and serotonergic (5-HT1D and 5-HT2A) receptors, synephrine may be one of the important components in the constrictive effects of Evodiae Fructus. Keywords:: Evodiae Fructus, synephrine, adrenergic α1, 5-hydroxytryptamine (5-HT)1D, 5-HT2A